2010 Annual International Conference of the IEEE Engineering in Medicine and Biology 2010
DOI: 10.1109/iembs.2010.5627842
|View full text |Cite
|
Sign up to set email alerts
|

Opto-electronic system for detection of flat foot by using estimation techniques: Study and approach of design

Abstract: Distribution of Foot Pressure reflects the deformations of body biomechanical design. They are caused by different reasons: degenerative, by trauma, etc., being flat foots a common pathology in Peru with high incidence. However there isn't the properly technology to detect properly this disease because is detected by a non-reliable visual way using pedoscopes. Flat foot is the degree of internal plantar arch lack and is well observed in foot pressure distribution. This distribution can be obtained by optical o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 4 publications
0
4
0
Order By: Relevance
“…The degree of foot deformity could be diagnosed and classified into seven levels based on the ratio between these areas. In his work [ 130 ], Luis A. Navarro developed a flatfoot detection platform consisting of a webcam and six FSR sensors, aiming to provide comprehensive information about the foot structure. The webcam collected data on arch length and width, while the force sensors measured the pressure at discrete plantar regions.…”
Section: Six Chronic Diseases and Corresponding Insole Systemsmentioning
confidence: 99%
“…The degree of foot deformity could be diagnosed and classified into seven levels based on the ratio between these areas. In his work [ 130 ], Luis A. Navarro developed a flatfoot detection platform consisting of a webcam and six FSR sensors, aiming to provide comprehensive information about the foot structure. The webcam collected data on arch length and width, while the force sensors measured the pressure at discrete plantar regions.…”
Section: Six Chronic Diseases and Corresponding Insole Systemsmentioning
confidence: 99%
“…Based on the ratio between the two areas, the foot deformity degree can be diagnosed and classified into 7 levels. In his work [88], Luis A. Navarro developed a flatfoot detection platform, composed of a webcam and 6 FSR sensors, to provide more comprehensive information about the foot structure. The webcam collected information on arch length and width, and the force sensors were used to obtain the pressure at discrete plantar regions.…”
Section: Flatfootmentioning
confidence: 99%
“…It has been suggested that the traditional visual judgment of flatfoot was too subjective, and that flatfoot should be detected by objective and accurate optical or electronic systems [ 23 ]. This study suggested how to design the insole-based plantar pressure instrument for flatfoot.…”
Section: Introductionmentioning
confidence: 99%